2017
DOI: 10.1016/j.vetmic.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Survey for selected pathogens in wild pigs ( Sus scrofa ) from Guam, Marianna Islands, USA

Abstract: Pigs (Sus scrofa) were introduced to Guam in the 1600's and are now present in high densities throughout the island. Wild pigs are reservoirs for pathogens of concern to domestic animals and humans. Exposure to porcine parvovirus, transmissible gastroenteritis, and Leptospira interrogans has been documented in domestic swine but data from wild pigs are lacking. The close proximity of humans, domestic animals, and wild pigs, combined with the liberal hunting of wild pigs, results in frequent opportunities for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…The common ancestor for PCV3 and PorkNW2/USA/2009 is a bat‐associated circovirus (BtRa‐CV/JS2013, KJ641724), and the mean divergence time was estimated approximately at 1802.6 (1774.3–1861.7, 95% HPD). Wild pigs are reservoirs for various pathogens, and these pathogens be transmitted to domestic pigs in close proximity to humans (Barrios‐Garcia & Ballari, ; Cleveland et al., ). We conjecture that PCV3 may have originated as a result of the bat‐associated circovirus cross‐species transition from bats into swine approximately 215 years ago.…”
Section: Resultsmentioning
confidence: 99%
“…The common ancestor for PCV3 and PorkNW2/USA/2009 is a bat‐associated circovirus (BtRa‐CV/JS2013, KJ641724), and the mean divergence time was estimated approximately at 1802.6 (1774.3–1861.7, 95% HPD). Wild pigs are reservoirs for various pathogens, and these pathogens be transmitted to domestic pigs in close proximity to humans (Barrios‐Garcia & Ballari, ; Cleveland et al., ). We conjecture that PCV3 may have originated as a result of the bat‐associated circovirus cross‐species transition from bats into swine approximately 215 years ago.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, antibodies against Brucella spp. in wild pigs in Guam, Marianna Islands, USA, were detected in 2.2% of animals tested (Cleveland et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…We found that adult males were more likely to be seropositive for IAVS (Figure ). None of the previous four studies investigating differences in exposure risk for males and females have found an association, although these studies were conducted under different circumstances (Cleveland et al, ; Feng et al, ; Martin et al, ; Pedersen et al, ). While the effect of age on IAVS seroprevalence has been found to be unimportant in most studies (Figure , Appendix ), our results supported two previous studies that found similar effects (Cleveland et al, ; Feng et al, ) and are consistent with IAVS risk factors in domestic pigs (Richt et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Wild pigs in North America are considered one of the most important host species for transmission of pathogens to humans, domestic animals, and wildlife (Bevins, Pedersen, Lutman, Gidlewski, & Deliberto, ; Miller et al, ) receiving significant policy implementation to mitigate disease risks (Miller, Opp, & Webb, ). Since previous studies have found demographic factors (age and sex) to be associated with increased or decreased probability of infection (e.g., Cleveland et al, ; Feng et al, ), we evaluated these effects on seroprevalence. Additionally, we assessed the effect of accounting for detection error in models of seroprevalence and how this may affect interpretation of risk factor associations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation